Evaluation of Virtual Desktop Infrastructure host using User Workload Simulator - Syahrul A. C., Abdullah; Muhammad F. M., Nazri; H. C. Soh, Zainal; Kamal Z., Zamli (2015)
Increasing cost and complexity of maintaining physical computers have caused large organization to consider alternative solution such as implementing Virtual Desktop Infrastructure (VDI) in their enterprise network. However, before deploying VDI solution in a large scale, it is essential to evaluate the sufficiency of the solution first. As a result, User Workload Simulator was developed. The simulator was used to evaluate two VDI solutions that are named VDI A and VDI B. The objective of the evaluation is to compare which solution can be a better VDI server host. From the result, VDI A is sufficiently better than VDI B for VM density per host. But in terms of network bandwidth utilization and Input/Output Operations Per Second (IOPS) consumption per host, VDI B is sufficiently better as it utilized less network bandwidth and consumed less IOPS on most of the user profiles evaluated.